Transição digital na construção civil: analisar a atividade de "levantamento de inconformidades" mediada por um aplicativo informático de uma diretora de obra - Elodie Chambonnière; Jacqueline Vacherand-Revel; Bruno Andrieu (Universidade do Porto, 2018)
The building sector is clearly undergoing the digital transition with the willingness to move from paper to absolute digital. Our research aims to study the transformation of the activity of "lifting of reservations" of a construction site manager using a business application. To grasp the complexity of this activity, a systemic approach seemed relevant and we proposed a theoretical articulation between the situated and incorporated dimensions of the activity and its historical-cultural development. We carried out an ethnographic investigation, for six months, in immersion on a construction site, in the form of an observant participation along with a shadowing observation. The main results indicate that the activity of "lifting of reservations" is part of a culture marked by the importance of the exchanges and the body. The business application transforms this activity which is sometimes strengthened, and other times thwarted. The construction site managers must adapt the use of the application to the site situations.